(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
Reforms in the field of education is one of the important priorities of any country. And access to the list of the best higher education institutions in the world ranking in the field of higher education is an important factor in the socio-economic development of the country. The article suggested that the reform of the education system is the main basis of social progress.